LARVAL ABUNDANCE, IDENTIFICATION AND PHYSICOCHEMICAL PROPERTIES OF THREE BREEDING HABITATS OF Aedes aegypti IN KANO METROPOLIS, KANO STATE - Aliyu, Umar; Tukur, Zainab (FUDMA JOURNAL OF SCIENCES, 2024)
Aedes aegypti is the primary vector for some arboviral diseases such as Yellow fever, dengue, zika and chikungunya. This specie of invasive mosquito has gained attention globally because of their fast-spreading trend and successful adaptation. This study was designed to determine the larval abundance and physic-chemical parameters of Aedes aegypti from three breeding sites within Kano metropolis. Determination of larval abundance was performed using ovitraps according to the protocol described by Wan-Norafikah et al., 2012. Twenty ovitraps were placed BUK old site, BUK New site and SOT from April – September, 2023. Physico-chemical parameters such as pH, Temperature, Electrical conductivity, Dissolved Oxygen, Total Dissolved Solids, Turbidity and Total Suspended Solids were measured for all breeding habitats. A total of 2959 Aedes aegypti larvae were collected in the study areas within Kano metropolis which comprised of BUK old site 31.80%, BUK New Site 32.75% and School of Technology (Kano Poly) 35.45%. The study revealed that temperature ranges from 29.98oC to 31.05oC, pH range of 6.37 – 6.74, TDS level of 109.80 – 305.09 mg/L and Electrical Conductivity ranges from 270 – 390 µS/cm. It can be concluded from this study that Aedes aegypti are abundant in the study area and also physic-chemical parameters of the breeding habitats showed significant variations among the three breeding habitats. This data may help in management of Aedes aegypti especially in eliminating stagnant water which serves as the breeding habitat.